The Hellenistic Settlements in Syria, the Red Sea Basin, and North Africa. - Cohen, Getzel M.
1 online resource (503 pages)
Keywords: This authoritative and sweeping compendium, the second volume in Getzel Cohen's organized survey of the Greek settlements founded or refounded in the Hellenistic period, provides historical narratives, detailed references, citations, and commentaries on all the settlements in Syria, The Red Sea Basin, and North Africa from 331 to 31 BCE. Organized geographically, the volume pulls together discoveries and debates from dozens of widely scattered archaeological and epigraphic projects. Cohen's magisterial breadth of focus enables him to provide more than a compilation of information; the volume also contributes to ongoing questions and will point the way toward new avenues of inquiry.